ANALYSIS OF GLOBAL ECONOMIC DEVELOPMENT AFTER THE COVID-19 PANDEMIC: CHALLENGES AND OPPORTUNITIES - Muhammad Juliansyah Putra (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This analysis evaluates global economic developments in the wake of the COVID-19 pandemic, focusing on the challenges and opportunities arising from this crisis. The pandemic led to economic contraction, supply chain disruptions and increased unemployment, forcing governments and businesses to adapt quickly in the face of uncertainty. While challenges such as widening economic disparities and the need for labour market stability remain, the crisis has also accelerated the trend towards digitalisation and innovation. New opportunities for economic recovery can be found in the technology, healthcare, renewable energy and logistics sectors. Adaptive responses and appropriate policies from governments as well as support for small and medium-sized enterprises (SMEs) are crucial in capitalising on this momentum for sustainable growth. With the right strategy, the global economy has the potential to recover and become stronger post-pandemic.